The Level of Farmer Household Food Security and the Influence of the Raskin Policy - Indri January (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
The purpose of this study was to (1) suspected the level of farmer household food security in the village of Tanjung Pering, (2) to explore the factors that influence household food security of farmers in the village of Tanjung Pering and (3) explore the influence policy giving rice to the poor (the rice)to the household food security of farmers in the village of Tanjung Pering. The research was conducted in the village of Tanjung Pering, District of North Inderalaya, Ogan Ilir. What research purposely determined in consideration of the community in the village of Tanjung Pering largely livelihood as farmers and rice for many distributed to the village. The results showed that the level of household food security of farmers in the village of Tanjung Pering, District of North Inderalaya, Ogan Ilir, which hold 53.33 percent food, 10 percent of food vulnerable and 36.67 percent less food. Factors that significantly influence the level of household food security of farmers in the village of Tanjung Pering, District of North Inderalaya, Ogan Ilir regency is the price of rice, the number of family members and income.